2021
DOI: 10.3390/ijerph18094623
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Unfavorable Treatment Outcomes among the Human Immunodeficiency Virus-Associated Tuberculosis Population in Tashkent City, Uzbekistan: 2013–2017

Abstract: Tuberculosis (TB) and human immunodeficiency virus (HIV) co-infection poses a growing clinical challenge. People living with HIV have a higher chance of developing TB, and once the disease has progressed, are at greater risk of having unfavorable TB treatment outcomes. Data on TB treatment outcomes among the HIV-associated TB population in Uzbekistan are limited. Thus, we conducted a cohort study among 808 adult patients with HIV-associated TB registered at the Tashkent TB referral hospital from 2013–2017 to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…TB-HIV co-infection is widely investigated and potentially threatening to the patient, as HIV makes its carrier susceptible to TB infections and complications due to the immunodeficiency caused by the virus in the body (18,21,22) . In this study, people with HIV received fewer healthcare actions compared to people who do not carry the virus.…”
Section: Discussionmentioning
confidence: 99%
“…TB-HIV co-infection is widely investigated and potentially threatening to the patient, as HIV makes its carrier susceptible to TB infections and complications due to the immunodeficiency caused by the virus in the body (18,21,22) . In this study, people with HIV received fewer healthcare actions compared to people who do not carry the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening TB/HIV control program integration is crucial to improve case management of TB–HIV co-infected patients. Studies conducted elsewhere that showed favorable treatment outcomes of between 79.8% [ 5 ] and 89.8% [ 15 ] can be achieved with the targeted clinical management of TB–HIV co-infected patients, specifically for those with other risks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies looking into factors associated with TB deaths have been carried out worldwide in high and low TB incidence countries, and have found important factors which include patients’ sociodemographic characteristics, TB disease characteristics, TB treatment characteristics, and underlying comorbidities [ 4 , 5 ]. However, the findings are different between countries and regions.…”
Section: Introductionmentioning
confidence: 99%
“…This point also supports extrapulmonary TB as a protective factor for retreatment episodes. Nevertheless, in most studies, it is thought that extrapulmonary TB is an independent risk factor for unfavorable events ( 39 42 ). The disagreement may be attributed to more care given to these patients and the rarity of severe forms of extrapulmonary TB [such as miliary TB (2.1 vs. 6.6%) and tuberculous meningitis (5.3 vs. 6.8%)], in comparison with data from Pang et al ( 43 ).…”
Section: Discussionmentioning
confidence: 99%